Abnormal causal connectivity of left superior temporal gyrus in drug-naïve first- episode adolescent-onset schizophrenia: A resting-state fMRI study. (30th September 2021) - Lyu, Hailong; Jiao, Jianping; Feng, Guoxun; Wang, Xinxin; Sun, Bin; Zhao, Zhiyong; Shang, Desheng; Pan, Fen; Xu, Weijuan; Duan, Jinfeng; Zhou, Qingshuang; Hu, Shaohua; et al.
Highlights: Brain function is abnormal in adolescents with schizophrenia. Adolescent schizophrenia can be recognized based on abnormal brain function. The early onset of schizophrenia is associated with brain dysfunction. Abstract: This study aimed to investigate the alterations of causal connectivity between the brain regions in Adolescent-onset schizophrenia (AOS) patients. Thirty-two first-episode drug-naïve AOS patients and 27 healthy controls (HC) were recruited for resting-state functional MRI scanning. The brain region with the between-group difference in regional homogeneity (ReHo) values was chosen as a seed to perform the Granger causality analysis (GCA) and further detect the alterations of causal connectivity in AOS. AOS patients exhibited increased ReHo values in left superior temporal gyrus (STG) compared with HCs. Significantly decreased values of outgoing Granger causality from left STG to right superior frontal gyrus and right angular gyrus were observed in GC mapping for AOS. Significantly stronger causal outflow from left STG to right insula and stronger causal inflow from right middle occipital gyrus (MOG) to left STG were also observed in AOS patients. Based on assessments of the two strengthened causal connectivity of the left STG with insula and MOG, a discriminant model could identify all patients from controls with 94.9% accuracy. This study indicated that alterations of directional connections in left STG may play an important role in the pathogenesis of AOS and serve as potential biomarkers for the disease.